Bunyavirus-Vector Interactions - Horne, Kate McElroy; Vanlandingham, Dana L. (My University, 2014)
The Bunyaviridae family is comprised of more than 350 viruses, of which many within the Hantavirus, Orthobunyavirus, Nairovirus, Tospovirus, and Phlebovirus genera are significant human or agricultural pathogens. The viruses within the Orthobunyavirus, Nairovirus, and Phlebovirus genera are transmitted by hematophagous arthropods, such as mosquitoes, midges, flies, and ticks, and their associated arthropods not only serve as vectors but also as virus reservoirs in many cases. This review presents an overview of several important emerging or re-emerging bunyaviruses and describes what is known about bunyavirus-vector interactions based on epidemiological, ultrastructural, and genetic studies of members of this virus family.
Citation: Horne, K.M.; Vanlandingham, D.L. Bunyavirus-Vector Interactions. Viruses 2014, 6, 4373-4397.
Keywords: Aedes Mosquito; Culex Mosquito; Bunyavirus; Hemorrhagic Fever; Tick